Trends in key African elephant populations - Iain Douglas-Hamilton (Pachyderm)
Presents the results of aerial surveys conducted in key elephant populations in Africa. In almost all the areas, the elephant population is greatly threatened by poaching. In north west Zaire large areas were devoid of elephants that had been killed by Arab poachers armed with automatic weapons. Elsewhere, as in Uganda, a severe decline was witnessed in the seventies, but poaching is being checked by the National Parks' Rehabilitation Programme backed by UNDP and EEC. Botswana is one of the few countries where elephant populations may be stable, as in Zimbabwe this is due to a strong government support for conservation policy.